The utility of radiographs prior to pin removal after operative treatment of supracondylar humerus fractures in children. (August 2015) - Schlechter, John A.; Dempewolf, Michael
Purpose: To determine the safety, utility, and efficacy of pin removal prior to radiographs during the postoperative care of surgically treated displaced pediatric supracondylar humerus fractures. Methods: Retrospective review of 532 children with supracondylar humerus fractures treated with closed reduction and pinning from 2007 to 2012. Group 1: children who had their splint/cast removed and radiographs prior to pin removal. Group 2: children with radiographs taken after removal. Data recorded and analyzed included: demographic and radiographic data at the time of surgery and at final follow-up, including the number of radiographs taken prior to pin removal and if pins were ever retained after radiographs were performed on the date of intended removal. Results: There was no difference between the groups' demographics. The number of postoperative radiographs taken prior to pin removal ranged from zero to two. No statistically significant change in Baumann's ( p = 0.79) or lateral humeral capitellar angles ( p = 0.19) was noted between the groups. No children in group 1 (0/438) had their pins retained after radiographs were taken on the date of intended removal. Conclusion: Obtaining postoperative radiographs prior to pin removal, although commonplace, is not necessary. If fracture stability is noted intraoperatively, and there is an uneventful postoperative course, it is safe and effective to discontinue immobilization and remove pins prior to X-ray. This is safely done without change in alignment or clinical sequelae. Doing so can aid in clinic flow, may decrease child anxiety, and limit multiple cast room visits. Level of evidence: Level III therapeutic study.